The challenges and opportunities in developing smart city: the construction practitioners’ perspectives - Wong, Jo Yee (2021)
Rapid urbanisation and overpopulation are global issues. The breakneck pace of urbanisation and overpopulation brought numerous problems to the existing city such as lack of accommodation, traffic congestion and environmental problems. Smart city concept is one of the optimal solutions applied by many countries to overcome the problem of the existing city. Previous studies were carried out on the smart city concept. Nonetheless, there are limited studies focused on the smart city concept in Malaysia. On top of that, as the smart city concept varies in different countries due to social, geographical, economic, environmental and political differences. Thus, the smart city concept adopted in other countries may not suit to adopt in Malaysia. Thus, this study aims to uncover the smart city implementation in Malaysia from the perspective of construction parties in Kuala Lumpur and Selangor. Four (4) aspects of problems of the existing city, five (5) aspects of opportunities of implementing smart city and five (5) aspects of challenges of implementing smart city were identified through literature review. Questionnaire surveys were sent to the construction practitioners in Kuala Lumpur and Selangor. 129 responses were returned and analysed by using Cronbach’s Alpha Reliability test, Arithmetic Mean test, Spearman’s Correlation test and Mann-Whitney U Test. The results revealed that the respondents perceived that traffic congestion was the most severe problem in the existing city; minimisation the construction and maintenance cost was the most possible opportunity of implementing smart city while poor planning was the most potential challenge of implementing smart city. The results of Spearman’s Correlation test showed that overpopulation was the most significant problem, minimisation of the deadlocks in the parking problems and offered a better quality of services for the citizens was the most noteworthy opportunity, and the current technology did not consider the variety and complication of the system was the most momentous challenge in three relationships. This study also demonstrated that there were significant differences across different current residential states on three objectives. The findings in this study would benefit the Malaysian government, professional bodies, non-profit organisation and researchers to aware the problems of the vi existing city, opportunities and challenges of implementing smart city in Malaysia which in turn could assist in smart city development.